Preparation method of high power density negative electrode material for lithium ion battery
By using fluidized bed processing and sintering methods in lithium-ion batteries, a high-power density negative electrode material is prepared, which solves the problems of low charge and discharge efficiency and poor circulation performance of traditional graphite materials, and achieves better battery performance.
Patent Information
- Application Number
- CN202111331852.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-11
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2041-11-11
AI Technical Summary
The graphite materials used in traditional lithium-ion batteries are low in lithium embedded space, resulting in low charging and discharging efficiency and poor circulation performance, which cannot meet the needs of high power density.
A method for preparing a high-power density negative electrode material for lithium-ion batteries is adopted, including mixing and grinding a binder, conductive agent and solvent to form a liquid conductive coating agent; then mixing with a soft carbon precursor with a small particle size and fluidizing treatment in a fluidized bed to form a porous structure; then sintering is carried out in a nitrogen atmosphere protection furnace to form a high-power density negative electrode material.
The negative electrode material prepared by this method has excellent capacity performance, cycle performance, first charge and discharge efficiency and rate performance, which significantly improves the overall performance of lithium-ion batteries.
Smart Images

Figure BDA0003349178810000091
Abstract
Description
Technical Field
[0001] The invention relates to the field of negative electrode materials, and in particular to a method for preparing a high power density negative electrode material for a lithium ion battery. Background Art
[0002] Lithium-ion batteries have been widely used in various fields in recent years due to their advantages such as high specific energy, high operating voltage, wide application temperature range, low self-discharge rate, long cycle life, pollution-free and good safety performance.
[0003] Most traditional lithium batteries use graphite materials as negative electrode materials. Due to the high degree of graphitization and highly layered structure of graphite materials, the lithium insertion space is small, resulting in a low lithium insertion capacity of graphite, which in turn leads to low charging and discharging efficiency of lithium-ion batteries, and poor cycle performance of graphite. Therefore, it is necessary to propose a new solution to improve the preparation method of high power density negative electrode materials for existing lithium-ion batteries. Summary of the invention
[0004] In view of this, the present invention aims to address the deficiencies in the prior art, and its main purpose is to provide a method for preparing a high power density negative electrode material for a lithium ion battery, wherein the prepared lithium ion battery has excellent capacity performance, cycle performance, first charge and discharge efficiency, and rate performance.
[0005] To achieve the above purpose, the present invention adopts the following technical solutions:
[0006] A method for preparing a high power density negative electrode material for a lithium ion battery, characterized in that it comprises the following steps:
[0007] Step (1): adding a binder, a conductive agent and a solvent in a certain proportion into a sand mill and grinding for 1 to 5 hours at a grinding speed of 500 to 2500 r / min to obtain a liquid conductive coating agent;
[0008] Step (2): selecting a soft carbon precursor with a small particle size and mixing it with a 5-30wt% strong acid or strong base solution, stirring it at 120-150° C. for 3-10 hours, filtering it and washing it thoroughly to obtain a soft carbon precursor with a porous structure;
[0009] Step (3): taking an appropriate amount of soft carbon precursor with a porous structure and placing it into a fluidized bed cavity, wherein the ratio of binder to soft carbon precursor with a porous structure is 3-6:100, introducing a carrier gas therein to fluidize the soft carbon precursor with a porous structure, and spraying the liquid conductive coating agent prepared in step (1) thereinto at an atomization speed of 1-10 g / min, so that the liquid conductive coating agent is evenly coated on the surface of the soft carbon precursor with a porous structure to form a conductive coating layer, thereby obtaining a coated soft carbon precursor;
[0010] Step (4): Place the coated soft carbon precursor obtained in step (3) in a nitrogen atmosphere protection furnace for sintering, increase the temperature to 1600-2000°C at a heating rate of 30-50°C / min and keep it warm for 2-5 hours, and obtain a high power density negative electrode material after crushing and screening.
[0011] As a preferred solution, the conductive agent is one or a mixture of carbon black, carbon nanotubes and graphene, and the carbon content thereof is above 99%.
[0012] As a preferred solution, the binder is one or a mixture of coal-based or oil-based asphalt, and its softening point is 50-200°C.
[0013] As a preferred embodiment, the solvent is one or a mixture of benzene, toluene and xylene.
[0014] As a preferred solution, the mass ratio of the binder, the conductive agent and the solvent is 1:0.05-0.5:0.5-2.0.
[0015] As a preferred solution, the soft carbon precursor is one or a mixture of crushed petroleum coke or needle coke, with D50=3-6 μm.
[0016] As a preferred embodiment, the carrier gas in step (3) is one or a mixture of nitrogen and argon, with a flow rate of 0.6-1.2 m / s. 3 / h, temperature is 160-200℃.
[0017] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, it can be seen from the above technical solution that:
[0018] By placing a soft carbon precursor with a porous structure into a fluidized bed chamber, using a carrier gas to fluidize the soft carbon precursor with a porous structure, and depositing a conductive agent on the surface of the soft carbon precursor with a porous structure by atomization, the interface impedance is further reduced, and the large current charge and discharge performance is improved. At the same time, the residual carbon content can be reduced to less than 2%, which improves the inactive sites on the soft carbon surface and the interface, so that the specific capacity, first efficiency, power performance and cycle performance of the negative electrode material can be greatly improved.
[0019] In order to more clearly illustrate the structural features and effects of the present invention, the present invention is described in detail below in conjunction with specific embodiments. DETAILED DESCRIPTION
[0020] The present invention discloses a method for preparing a high power density negative electrode material for a lithium ion battery, which comprises the following steps:
[0021] Step (1): Add a binder, a conductive agent, and a solvent into a sand mill in a certain proportion, wherein the mass ratio of the binder, the conductive agent, and the solvent is 1:0.05-0.5:0.5-2.0, wherein the conductive agent is a mixture of one or more of carbon black, carbon nanotubes, and graphene, and its carbon content is more than 99%, the binder is a mixture of one or more of coal-based or oil-based asphalt, and its softening point is 50-200°C, and the solvent is a mixture of one or more of benzene, toluene, and xylene. Grind for 1 to 5 hours at a grinding speed of 500-2500 r / min to obtain a liquid conductive coating agent.
[0022] Step (2): Select a soft carbon precursor with a small particle size and mix it with a 5-30wt% strong acid or strong base solution. The soft carbon precursor is a mixture of one or more of crushed petroleum coke or needle coke, D50 = 3-6μm, and stir at 120-150°C for 3-10h, filter and fully wash to obtain a soft carbon precursor with a porous structure.
[0023] Step (3): Take an appropriate amount of soft carbon precursor with a porous structure and put it into the fluidized bed cavity, wherein the ratio of binder to soft carbon precursor with a porous structure is 3-6:100, and introduce a carrier gas into the cavity to make the soft carbon precursor with a porous structure present a fluidized state, wherein the carrier gas is one or a mixture of nitrogen and argon, and the liquid conductive coating agent prepared in step (1) is sprayed into the cavity by atomization, and the atomization speed is 1-10 g / min, and the flow rate is 0.6-1.2 m 3 / h, the temperature is 160-200°C, so that it is evenly coated on the surface of the soft carbon precursor with a porous structure to form a conductive coating layer, and the coated soft carbon precursor is obtained.
[0024] Step (4): Place the coated soft carbon precursor obtained in step (3) in a nitrogen atmosphere protection furnace for sintering, increase the temperature to 1600-2000°C at a heating rate of 30-50°C / min and keep it warm for 2-5 hours, and obtain a high power density negative electrode material after crushing and screening.
[0025] The present invention is described below with specific examples and comparative examples.
[0026] Example 1
[0027] Step (1): Add a mixture of oil-based asphalt, carbon black, benzene and toluene into a sand mill in a certain proportion, wherein the mass ratio of the mixture of oil-based asphalt, carbon black, benzene and toluene is 1:0.5:0.5, the softening point of the oil-based asphalt is 50-200°C, the carbon content of carbon black is more than 99%, grind for 2 hours at a grinding speed of 2000 r / min to obtain a liquid conductive coating agent.
[0028] Step (2): Select small-particle-size crushed petroleum coke and mix it with 5wt% sodium hydroxide solution, where D50 of the petroleum coke is 3-6μm, and stir it at 150°C for 8h, filter it and wash it thoroughly to obtain a soft carbon precursor with a porous structure.
[0029] Step (3): Take an appropriate amount of petroleum coke with a porous structure and put it into the fluidized bed cavity, wherein the ratio of oil-based asphalt to petroleum coke with a porous structure is 3:100, and introduce a mixed gas composed of nitrogen and argon to make the petroleum coke with a porous structure in a fluidized state, and spray the liquid conductive coating agent prepared in step (1) into the fluidized bed cavity by atomization, at an atomization speed of 1 g / min and a flow rate of 0.6 m / s. 3 / h, the temperature is 200°C, so that it is evenly coated on the surface of the petroleum coke with a porous structure to form a conductive coating layer, and the coated petroleum coke is obtained.
[0030] Step (4): the coated petroleum coke obtained in step (3) is placed in a nitrogen atmosphere protection furnace for sintering, the temperature is raised to 1800° C. at a heating rate of 30° C. / min and kept warm for 3 hours, and a high power density negative electrode material is obtained after crushing and screening.
[0031] Example 2
[0032] Step (1): Add a mixture of oil-based asphalt, graphene, toluene and xylene into a sand mill in a certain proportion, wherein the mass ratio of the mixture of oil-based asphalt, graphene, toluene and xylene is 1:0.05:2, the carbon content of graphene is more than 99%, the softening point of the oil-based asphalt is 50-200°C, grind for 1 hour, and the grinding speed is 2500r / min to obtain a liquid conductive coating agent.
[0033] Step (2): selecting small-sized crushed needle coke and mixing it with 30 wt% sulfuric acid solution, wherein D50 of the needle coke is 3-6 μm, and stirring it at 120° C. for 10 h, filtering it and washing it thoroughly to obtain needle coke with a porous structure.
[0034] Step (3): Take an appropriate amount of porous needle coke and put it into the fluidized bed cavity, wherein the ratio of oil-based asphalt to porous needle coke is 6:100, introduce nitrogen into the cavity to make the porous needle coke present a fluidized state, and spray the liquid conductive coating agent prepared in step (1) into the cavity by atomization at an atomization speed of 10 g / min and a flow rate of 1.2 m / s. 3 / h, the temperature is 160°C, so that it is evenly coated on the surface of the needle coke with a porous structure to form a conductive coating layer, thereby obtaining the coated needle coke.
[0035] Step (4): the coated needle coke obtained in step (3) is placed in a nitrogen atmosphere protection furnace for sintering, the temperature is raised to 1800° C. at a heating rate of 40° C. / min and kept warm for 4 hours, and a high power density negative electrode material is obtained after crushing and screening.
[0036] Example 3
[0037] Step (1): Add a mixture of coal-based asphalt, carbon nanotubes and benzene into a sand mill in a certain proportion, wherein the mass ratio of the mixture of coal-based asphalt, carbon nanotubes and benzene is 1:0.5:0.5, the carbon content of the carbon nanotubes is more than 99%, the softening point of the coal-based asphalt is 50-200°C, grind for 5 hours at a grinding speed of 500r / min, and obtain a liquid conductive coating agent.
[0038] Step (2): selecting small-particle-size crushed petroleum coke and mixing it with 10 wt% sodium hydroxide solution, wherein the D50 of the petroleum coke is 3-6 μm, and stirring it at 130° C. for 6 h, filtering it and washing it thoroughly to obtain a petroleum coke with a porous structure.
[0039] Step (3): Take an appropriate amount of petroleum coke with a porous structure and put it into the fluidized bed cavity, wherein the ratio of coal-based asphalt to petroleum coke with a porous structure is 4:100, and introduce argon gas into the cavity to make the petroleum coke with a porous structure present a fluidized state, and spray the liquid conductive coating agent prepared in step (1) into the cavity by atomization, with an atomization speed of 6 g / min and a flow rate of 0.8 m / s. 3 / h, the temperature is 180°C, so that it is evenly coated on the surface of the petroleum coke with a porous structure to form a conductive coating layer, and the coated petroleum coke is obtained.
[0040] Step (4): the coated petroleum coke obtained in step (3) is placed in a nitrogen atmosphere protection furnace for sintering, the temperature is raised to 1600° C. at a heating rate of 50° C. / min and kept warm for 5 hours, and a high power density negative electrode material is obtained after crushing and screening.
[0041] Example 4
[0042] Step (1): Adding a mixture of oil-based asphalt, carbon black and graphene, and toluene into a sand mill in a certain proportion, wherein the mass ratio of the mixture of oil-based asphalt, carbon black and graphene, and toluene is 1:0.1:1, the carbon content of the mixture of carbon black and graphene is more than 99%, the softening point of the oil-based asphalt is 50-200°C, grinding for 3 hours at a grinding speed of 1500r / min, and obtaining a liquid conductive coating agent.
[0043] Step (2): selecting small-sized crushed needle coke and mixing it with 20 wt% sulfuric acid solution, wherein the D50 of the needle coke is 3-6 μm, and stirring it at 130° C. for 3 h, filtering it and washing it thoroughly to obtain needle coke with a porous structure.
[0044] Step (3): Take an appropriate amount of soft carbon precursor with a porous structure and put it into the fluidized bed cavity, wherein the ratio of oil-based asphalt to porous needle coke is 5:100, and introduce nitrogen into the cavity to make the porous needle coke present a fluidized state. The liquid conductive coating agent prepared in step (1) is sprayed into the cavity by atomization at a rate of 8 g / min and a flow rate of 1.0 m / min. 3 / h, the temperature is 190°C, so that it is evenly coated on the surface of the needle coke with a porous structure to form a conductive coating layer, thereby obtaining the coated needle coke.
[0045] Step (4): the coated needle coke obtained in step (3) is placed in a nitrogen atmosphere protection furnace for sintering, the temperature is raised to 2000° C. at a heating rate of 35° C. / min and kept warm for 2 hours, and a high power density negative electrode material is obtained after crushing and screening.
[0046] Example 5
[0047] Step (1): Add a mixture of coal-based asphalt, graphene, benzene and toluene into a sand mill in a certain proportion, wherein the mass ratio of the mixture of coal-based asphalt, carbon black, benzene and toluene is 1:0.3:1.5, the carbon content of graphene is more than 99%, the softening point of coal-based asphalt is 50-200°C, grind for 2 hours, and the grinding speed is 2000r / min to obtain a liquid conductive coating agent.
[0048] Step (2): select small-particle-size crushed petroleum coke and mix it with 5-30wt% sodium hydroxide solution, where D50 of the petroleum coke is 3-6μm, and stir it at 125°C for 8h, filter it and wash it thoroughly to obtain a soft carbon precursor with a porous structure.
[0049] Step (3): Take an appropriate amount of petroleum coke with a porous structure and put it into the fluidized bed cavity, wherein the ratio of coal-based asphalt to petroleum coke with a porous structure is 3:100, and introduce argon gas into the cavity to make the petroleum coke with a porous structure present a fluidized state, and spray the liquid conductive coating agent prepared in step (1) into the cavity by atomization, at an atomization speed of 3 g / min and a flow rate of 0.7 m / s. 3 / h, the temperature is 190°C, so that it is evenly coated on the surface of the petroleum coke with a porous structure to form a conductive coating layer, and the coated petroleum coke is obtained.
[0050] Step (4): the coated petroleum coke obtained in step (3) is placed in a nitrogen atmosphere protection furnace for sintering, the temperature is raised to 1700° C. at a heating rate of 35° C. / min and kept warm for 4 hours, and a high power density negative electrode material is obtained after crushing and screening.
[0051] Example 6
[0052] Step (1): Add a mixture of coal-based asphalt, carbon nanotubes and xylene into a sand mill in a certain proportion, wherein the mass ratio of the mixture of coal-based asphalt, carbon nanotubes and xylene is 1:0.2:1.8, the carbon content of the carbon nanotubes is more than 99%, and the softening point of the coal-based asphalt is 50-200°C. Grind for 3 hours at a grinding speed of 1800 r / min to obtain a liquid conductive coating agent.
[0053] Step (2): selecting small-sized crushed needle coke and mixing it with 15 wt% sulfuric acid solution, wherein D50 of the needle coke is 3-6 μm, and stirring it at 145° C. for 7 h, filtering it and washing it thoroughly to obtain needle coke with a porous structure.
[0054] Step (3): Take an appropriate amount of needle coke with a porous structure and put it into the fluidized bed cavity, wherein the ratio of coal-based asphalt to needle coke with a porous structure is 3-6:100, and introduce nitrogen into the cavity to make the needle coke with a porous structure present a fluidized state, and spray the liquid conductive coating agent prepared in step (1) into the cavity by atomization, at an atomization speed of 4 g / min and a flow rate of 0.9 m / s. 3 / h, the temperature is 190°C, so that it is evenly coated on the surface of the needle coke with a porous structure to form a conductive coating layer, thereby obtaining the coated needle coke.
[0055] Step (4): the coated needle coke obtained in step (3) is placed in a nitrogen atmosphere protection furnace for sintering, the temperature is raised to 1950° C. at a heating rate of 38° C. / min and kept warm for 3 hours, and a high power density negative electrode material is obtained after crushing and screening.
[0056] Comparative Example 1
[0057] Binder: soft carbon precursor = 0.5-2:100. The soft carbon precursor is directly coated and then carbonized to obtain the negative electrode material.
[0058] Comparative Example 2
[0059] Negative electrode material obtained by coating soft carbon precursor without adding conductive agent
[0060] Electrochemical performance test
[0061] In order to detect the performance of the negative electrode material of the lithium ion battery of the negative electrode material of the present invention, the half-cell test method is used to test, the negative electrode material of the above embodiment and comparative example: SBR (solid content 50%): CMC: Super-p = 95.5: 2: 1.5: 1 (weight ratio), add appropriate amount of deionized water to mix into a slurry, apply it on copper foil and dry it in a vacuum drying oven for 12 hours to make a negative electrode sheet, the electrolyte is 1MLiPF6 / EC+DEC+DMC=1: 1: 1, the polypropylene microporous membrane is the diaphragm, the counter electrode is a lithium sheet, and the battery is assembled. The constant current charge and discharge experiment is carried out in the LAND battery test system, the charge and discharge voltage is controlled at 0.01-3.00V, and the data is collected and controlled by a computer-controlled charge and discharge cabinet. The test results are shown in Table 1.
[0062] Table 1
[0063]
[0064] According to the data in Table 1, the high power density negative electrode material prepared by the present invention has excellent capacity performance, cycle performance, first charge and discharge efficiency and rate performance. The double carbon layer structure formed by the conductive agent and the binder plays a very critical role, reducing the interface impedance and improving various performances.
[0065] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a high power density negative electrode material for a lithium ion battery, characterized in that: The following steps are involved: Step (1): adding a binder, a conductive agent, and a solvent in a certain proportion to a sand mill and grinding for 1 to 5 hours at a grinding speed of 500-2500 r / min to obtain a liquid conductive coating agent, wherein the conductive agent is a mixture of one or more of carbon black, carbon nanotubes, and graphene, and the carbon content thereof is more than 99%, and the mass ratio of the binder, the conductive agent, and the solvent is 1:0.05-0.5:0.5-2.0; Step (2): selecting a soft carbon precursor with a small particle size and mixing it with a 5-30wt% strong acid or strong base solution, stirring it at 120-150° C. for 3-10 hours, filtering it and washing it thoroughly to obtain a soft carbon precursor with a porous structure; Step (3): Take an appropriate amount of soft carbon precursor with a porous structure and put it into the fluidized bed chamber, wherein the ratio of binder to soft carbon precursor with a porous structure is 3-6:100, and introduce a carrier gas into the fluidized bed to make the soft carbon precursor with a porous structure present a fluidized state, wherein the carrier gas is one or a mixture of nitrogen and argon, and the flow rate is 0.6-1.2m 3 / h, the temperature is 160-200°C, and the liquid conductive coating agent prepared in step (1) is sprayed into the mixture at an atomization speed of 1-10g / min, so that the liquid conductive coating agent is evenly coated on the surface of the soft carbon precursor having a porous structure to form a conductive coating layer, thereby obtaining a coated soft carbon precursor; Step (4): Place the coated soft carbon precursor obtained in step (3) in a nitrogen atmosphere protection furnace for sintering, increase the temperature to 1600-2000°C at a heating rate of 30-50°C / min and keep it warm for 2-5 hours, and obtain a high power density negative electrode material after crushing and screening.
2. The method for preparing a high power density negative electrode material for a lithium ion battery according to claim 1, characterized in that: The binder is one or a mixture of coal-based or oil-based asphalt, and its softening point is 50-200°C.
3. The method for preparing a high power density negative electrode material for a lithium ion battery according to claim 1, characterized in that: The solvent is one or a mixture of benzene, toluene and xylene.
4. The method for preparing a high power density negative electrode material for a lithium ion battery according to claim 1, characterized in that: The soft carbon precursor is one or a mixture of crushed petroleum coke or needle coke, and D50 is 3-6 μm.
Citation Information
Patent Citations
Carbon / carbon composite microsphere material, production method and lithium ion battery
CN103214245A
Method of making composite particle for electrode, method of making electrode, method of making electrochemical device, apparatus for making thereof
CN1591935A